2017
DOI: 10.1021/acsami.7b00174
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Water Channels for Enhanced Ion Transport in 14 nm Diameter Carbon Nanotubes

Abstract: Ion transport plays an important role in solar-to-electricity conversion, drug delivery, and a variety of biological processes. Carbon nanotube (CNT) is a promising material as an ion transporter in the applications of the mimicking of natural ion channels, desalination, and energy harvesting. Here, we demonstrate a unique, enhanced ion transport through a vertically aligned multiwall CNT membrane after the application of an electric potential across CNT membranes. Interestingly, electrowetting arising from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…An obvious bottleneck of our model is neglecting diffusion limitations, which complicates a possible experimental verification of theoretical predictions. However, recently a considerable progress has been attained in experimental studies of molecular diffusion in ultra‐narrow carbon nanotubes [45–49] . Most of these experiments were performed with nanofluidic devices where a SWCNT (with diameter of 1.5–1.6 nm and the length of ca 20 μm) spans a barrier separating electrolyte reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious bottleneck of our model is neglecting diffusion limitations, which complicates a possible experimental verification of theoretical predictions. However, recently a considerable progress has been attained in experimental studies of molecular diffusion in ultra‐narrow carbon nanotubes [45–49] . Most of these experiments were performed with nanofluidic devices where a SWCNT (with diameter of 1.5–1.6 nm and the length of ca 20 μm) spans a barrier separating electrolyte reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“… 10 In particular, wetting/dewetting via changes in externally applied E-fields is an attractive prospect for direct control of gating in novel nanopores. An experimental study 238 has demonstrated the influence of an applied electric potential on water affinity for the interior walls of a CNT channel 14 nm in diameter. Simulation studies of the effect of an external E-field on the wetting of a hydrophobic gate in a simplified model of a membrane protein 239 (discussed in more detail below) demonstrate that these effects of E-field on wetting can also be seen in a protein nanopore environment.…”
Section: Simplified Models Of Nanoporesmentioning
confidence: 99%
“…Obviously, any biological applications of phosphorene require in-depth understanding of its interaction with biomolecules and fluids. In recent years, the wetting and diffusion behaviors of water in/on nanomaterials, such as graphene, carbon nanotube, boron-nitride, WS 2 , and MoS 2 have been extensively studied. We note, however, that the research on the interfacial behavior of water on phosphorene has just started. , Although the wetting and diffusion behaviors of water droplets (with a fixed number of water molecules) on pristine phosphorene surfaces have been studied, , the macroscopic contact angle of water droplets on phosphorene remains unexplored.…”
Section: Introductionmentioning
confidence: 99%